Penjatuhan Pidana Terhadap Penyalahguna Narkotika Untuk Diri Sendiri (Studi Putusan Pengadilan Negeri Lubukpakam No. 1100/Pid.Sus/2016/PN.Lbp Dan Putusan Pengadilan Negeri Semarang No. 529/Pid.Sus/2016/PN.Smg) - Bornok Simanjuntak; Madiasa Ablisar; Mahmud Mulyadi; Edy Ikhsan (Universitas Sumatera Utara, 2019)
Abstract. The imposition of imprisonment for abusers or narcotics addicts becomes less optimal when the number of prison capacity or state detention centers becomes over capacity because the occupants are dominated by addicts and drug abusers.Keywords: narcotics abuse, prison and rehabilitation crimes